(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
In this article, the personal content of the personal content is revealed based on the analysis of the problems of taxation of the income received from Uzbekistan and the content of their legal development, the importance of this process. Specific legal norms of the materials in this article are studied.